Evaluating Pennsylvania Pharmacists' Provision of Community-based Patient Care Services to Develop a Statewide Practice Network - Maria A. Osborne, PharmD; Margie E. Snyder, PharmD, MPH; Deanne L. Hall, PharmD, CDE; Kim C. Coley, PharmD, FCCP; Melissa Somma McGivney, PharmD, FCCP (University of Minnesota Libraries Publishing, 2011)
Objective: To identify and describe Pennsylvania pharmacists who currently provide or are interested in providing community-basedpatient care services and are interested in joining a statewide practice network. Design: Cross-sectional survey. Setting: February toJune 2009 in Pennsylvania. Participants: 1700 pharmacists. Intervention: Mailed and electronic survey. Main outcome measures:Number and geographic location of pharmacists providing or interested in providing community-based patient care in Pennsylvania.Description of patient care documentation methods; physical space; services provided; perceived barriers to providing patient care;training needs; and interest in joining a statewide practice network. Results: The final analysis included data from 1700 pharmacists.Approximately one-third of pharmacists (n=554) were providing patient care services to community-based patients. Most wereroutinely documenting (67.5%) and many had a semi-private or private space to provide care. MTM and immunizations were themost common services provided. Respondents reported the most significant barrier to providing MTM, diabetes education, andsmoking cessation education was time constraints, whereas training was a barrier for immunization provision. Most pharmacistswere not being compensated for patient care services. Of the 869 pharmacists interested in joining a statewide network, thoseproviding care were more interested in joining than those who were not (70.8% vs. 43.8%, p < 0.001). Conclusion: Pennsylvaniapharmacists are interested in providing community-based patient care services and joining a statewide practice network focused onproviding community-based patient care services. This research serves as a foundation for building a pharmacist practice network inPennsylvania.